Development of E-LKPD Based on A Scientific Approach for Students of MAN 2 Model Medan - Razid Ananda Siregar (Indonesian Journal of Advanced Research, 2023)
This study aims to develop an E-LKPD based on a scientific approach at MAN 2 Model Medan. The results of this study are in the form of an Electronic Student Worksheet (E-LKPD). Data collection using validation questionnaires, practical questionnaires, student activity sheets, and student response questionnaires to E-LKPD based on a scientific approach. The trial of the E-LKPD was carried out face-to-face in Class X-4 at the MAN 2 Model school. The results of this development research are an E-LKPD based on a scientific approach for students of MAN 2 Model Medan showing that: (1) The E-LKPD developed is stated to be valid based on the assessment of experts and math teachers with an average validity rating of 84.23% with a score "Valid", (2) E-LKPD based on a scientific approach was declared practical based on an assessment from a mathematics teacher with a proportion of 81.73% and an assessment from students X-4 MAN 2 Model with a proportion of 92.8%, (3) E- LKPD based on a scientific approach has been declared effective based on an assessment from the student response questionnaire with a score of 84% and an assessment from the student activity observation sheet with a value of 88.15 and categorized as very positive. From the results of the analysis above, it can be interpreted that the E-LKPD based on the scientific approach of the Medan Model MAN 2 students is valid, practical, and effective in using the E-LKPD in schools.